2002
DOI: 10.1002/bip.10312
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular domains of the neurokinin‐1 receptor: Structural characterization and interactions with substance P

Abstract: The technical difficulties associated with the structure determination of membrane proteins have limited the structural information available for the ligand binding to G-protein coupled receptors (GPCRs). Here, we describe a reductionist approach to GPCR structure determination in which the extracellular domains of the receptor are examined by high-resolution NMR in the presence of a membrane mimetic. The resulting structural features are then incorporated into a molecular model of the receptor, utilizing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Attempts have been made to overcome these drawbacks using traditional NMR, but with synthetic peptides selected to represent critical receptor domains, mainly extracellular loops with a part of TMs (Boivin et al, 2008;Giragossian & Mierke, 2001;Giragossian & Mierke, 2002;Giragossian, Schaschke, Moroder, & Mierke, 2004;Giragossian, Sugg, Szewczyk, & Mierke, 2003;Pellegrini & Mierke, 1999;Ulfers, Piserchio, & Mierke, 2002). Even if such an approach is not fully satisfactory, it can provide relevant structural information, as demonstrated by several studies showing that the secondary structures observed were close to those obtained byX-ray crystallography when the structure of the whole receptor was available (Albert & Yeagle, 2000, 2002Katragadda, Alderfer, & Yeagle, 2000).…”
Section: Please Scroll Down For Articlementioning
confidence: 70%
See 1 more Smart Citation
“…Attempts have been made to overcome these drawbacks using traditional NMR, but with synthetic peptides selected to represent critical receptor domains, mainly extracellular loops with a part of TMs (Boivin et al, 2008;Giragossian & Mierke, 2001;Giragossian & Mierke, 2002;Giragossian, Schaschke, Moroder, & Mierke, 2004;Giragossian, Sugg, Szewczyk, & Mierke, 2003;Pellegrini & Mierke, 1999;Ulfers, Piserchio, & Mierke, 2002). Even if such an approach is not fully satisfactory, it can provide relevant structural information, as demonstrated by several studies showing that the secondary structures observed were close to those obtained byX-ray crystallography when the structure of the whole receptor was available (Albert & Yeagle, 2000, 2002Katragadda, Alderfer, & Yeagle, 2000).…”
Section: Please Scroll Down For Articlementioning
confidence: 70%
“…For the N-terminus, two explanations can be put forward: (i) there are not enough amino acid residues from the preceding TM6 to generate the expected helix because 3.6 amino acids are necessary in one alpha helix turn and (ii) the end of TM6 could be shifted toward the N-terminus and thus is absent from the synthesized peptide. Indeed, this type of discrepancy between the experimental structure and the models calculated from multiple protein sequence alignments has already been observed (Ma, Liu, Li, Tang, & Xu, 2005;Piserchio, Bisello, Rosenblatt, Chorev, & Mierke, 2000;Ulfers et al, 2002). To date, we cannot exclude either of these two hypotheses.…”
Section: Hnts1(321-344) Receptor Fragmentmentioning
confidence: 80%
“…This conclusion is supported by our observation of change in line widths of hydrophobic side chains in DPC micelles and is in agreement with receptor modeling studies that shows for SP that this region interacts with the transmembrane portions of the receptor. [57][58][59][60] The selectivity of these ligands to different NK receptors has been suggested to be in the N-terminus of these ligands that vary in their sequence among the ligands that selectively bind to the three receptors. Because SP is the mammalian tachykinin that binds selectively to NK 1 receptor, several mutagenesis and Ala scan studies have been carried out on SP.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these methods are therefore highly complementary, with strong potential for combined use. (Pellegrini and Mierke 1999 b (Inooka et al 2001) c (Sun et al 2007) d (Ulfers et al 2002) e (Luca et al 2003) f (Mesleh et al 2007) g h (Grace et al 2007) i (Parthier et al 2007) j (Lopez et al 2008) k l (Runge et al 2007) m (Underwood et al 2010) …”
Section: Discussionmentioning
confidence: 99%
“…A concentration-dependent shifting of several resonances in the one-dimensional spectrum of SP upon addition of a fragment of NK-1R (264-290) was observed, indicating a ligand-specific and reversible binding of SP to the NK-1R(264-290) in the peptide:ligand ratio of 1:1. This was combined with twodimensional NOE spectroscopy (NOESY) experiments, homology modelling and photoaffinity labelling results to determine a putative bound state conformation (Macdonald et al 2001, Ulfers et al 2002.…”
Section: Chemical Shift Perturbationmentioning
confidence: 99%